If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = c + 7 + -13 Reorder the terms: 3 = 7 + -13 + c Combine like terms: 7 + -13 = -6 3 = -6 + c Solving 3 = -6 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 3 + -1c = -6 + c + -1c Combine like terms: c + -1c = 0 3 + -1c = -6 + 0 3 + -1c = -6 Add '-3' to each side of the equation. 3 + -3 + -1c = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -1c = -6 + -3 -1c = -6 + -3 Combine like terms: -6 + -3 = -9 -1c = -9 Divide each side by '-1'. c = 9 Simplifying c = 9
| 5x+6=5x+6 | | 0.5d-3b+5=0 | | 4(x+4)+6=4x+6 | | 5x-17+3x=5x+2 | | (5b-1)-2(2b+1)=-6 | | 3x+7=2x+x | | 70/10 | | -35v=21 | | 6+w/-8=4/7 | | x(x+5)=234 | | 3(x-5)=2(2x+7) | | 3m-5=8m+6 | | 2/3+3m/5=31/51 | | 2y-10/2=5 | | x(-7)-2=10 | | 4x^2+5xy+12z+15y= | | -10x^2+3x-4=0 | | x(-7)+2=10 | | 4/9=x-3/6 | | 3/5x+4/10x=36/15 | | |5g+8|=33 | | 6x^4-x^2-12=0 | | 4(3a-2)=10a-(8-2a) | | 42=7/6x | | -15+2000=-17+2x-x | | 0.3x-7=1.1x-15 | | 4w=84 | | -15+2000=17-2x | | 12=w | | -5n+6=41 | | -6x-36=-5 | | 34x=-9 |